2019
DOI: 10.21203/rs.2.9887/v5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Constructing an Experiential Education Model in Undergraduate Radiology Education by the Utilization of the Picture Archiving and Communication System (PACS)

Abstract: Background Medical education in China is in a transitional period changing from passive learning to experiential education models. We have modified an experiential education method for radiology education. The aim of this study is to evaluate the effect of this method on undergraduate radiology education. Methods With the help of the picture archiving and communication system (PACS) and RadiAnt DICOM Viewer, we have modified an experiential education method that simulates similar working conditions for undergr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Audience response system has increased students' participation as a good interactive strategy of classroom teaching (22,34). Hybrid of CBL and the PACS simulator mimics clinical scenarios and motivates students to see, think, and behave as genuine doctors, in which students could be trained on problem solving and diagnostic reasoning, as well as increase their self-confidence (35,36). Under the concept of immersion and simulation, these methods were organized systematically upon the smart class environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Audience response system has increased students' participation as a good interactive strategy of classroom teaching (22,34). Hybrid of CBL and the PACS simulator mimics clinical scenarios and motivates students to see, think, and behave as genuine doctors, in which students could be trained on problem solving and diagnostic reasoning, as well as increase their self-confidence (35,36). Under the concept of immersion and simulation, these methods were organized systematically upon the smart class environment.…”
Section: Discussionmentioning
confidence: 99%
“…First, we used a CBL pattern during course delivery, where teacher disclosed image-related information step by step. Similarly, Chen et al (35) used cases in simulator-based teaching, but self-learning was the main body and imaging information was open. Students with our model experienced the process of diagnostic formulation and decision making in a manner similar to doctors.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 Self-assessment questionnaires can help researchers gain important insights and influence personal attributes and attitudes. 32,33 A presurvey and postsurvey study showed that a health care curriculum had positive effects on students' attitudes, perceptions, and communications skills. 32 Nevertheless, future programs will need to apply objective methods to assess the effectiveness of educational interventions in oncology and use that as an opportunity for further development and improvement.…”
Section: Discussionmentioning
confidence: 99%
“…The picture archiving and communication systems (PASC) is an integral part of the medical information system, which can obtain medical images for imaging diagnosis. In addition, it also can measure, reconstruct, and calculate the images through the image processing tool of workstation, which can provide effective guidance in clinical treatment practice [7,8]. In recent years, medical image processing technology has become more and more critical with the rapid development of modern medical image technology.…”
Section: Introductionmentioning
confidence: 99%